Strategi Kebijakan untuk Menyelaraskan Pendidikan dengan Kebutuhan Pelestarian Budaya - Wayan Pait (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy article examines the urgency of revitalizing the curriculum of Hindu Religious Higher Education Institutions to optimize contributions to cultural preservation. The main issues identified are the gap between the theology-focused curriculum and practical needs in the field, the lack of incentives for lecturers, and limited inter-institutional collaboration, resulting in PTKH graduates lacking practical competencies and leaving Hindu cultural heritage vulnerable to erosion by modernization. This paper uses qualitative methods with a descriptive analysis approach and USG (Urgency, Seriousness, Growth) analysis, as well as William N. Dunn's theory and cost-benefit model to evaluate various policy alternatives. The analysis results indicate that curriculum revitalization is the most fundamental and efficient solution, as it has low implementation costs but very high long-term benefits, namely producing graduates with dual competencies and strong cultural awareness. The proposed policy recommendation is the issuance of a Rector's Regulation that explicitly integrates material on the preservation of intangible and tangible culture into the curriculum of all study programs. This regulation also needs to be supported by an incentive system that recognizes lecturers' contributions to cultural preservation. Thus, PTKH will be able to strengthen its role as a center of knowledge and the vanguard in preserving Hindu cultural heritage in Indonesia.